CHAPTER 4: THE MEETING AS DECISION MAKING ON PRODUCTION. (AmeriQuests, 2016)
Chapter 4 of the book “Workers and Decision Making on Production" is presented which explores the impact of worker's decision making in production and the productive operation of the plant.